2015
DOI: 10.3390/publications3010027
|View full text |Cite
|
Sign up to set email alerts
|

Apprenticeship in Scholarly Publishing: A Student Perspective on Doctoral Supervisors’ Roles

Abstract: Abstract:Although a large body of literature has suggested that doctoral supervisors play an important role in their students' attempts at scholarly publishing, few studies have focused specifically on what roles they play. This study sought to address this gap by zooming in on the various roles a group of Chinese doctoral students found their supervisors playing in their scholarly publishing endeavors. Our analysis revealed four important roles played by the supervisors: 'prey' searchers, managers, manuscript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 46 publications
1
27
1
1
Order By: Relevance
“…However, what has not yet been as widely reported in the ERPP research to date is the extent to which the role of the supervisor is conducive to the fostering of publishing scholars beyond the supervisor-student relationship. To that extent, the research reported here contributes to furthering insight into that relationship, and is consistent with Lei and Hu's recent study in China [21], in which a similar proportion of participants (only 2 of 11 supervisees) reported any sort of systematic publishing guidance by supervisors.…”
Section: Discussionsupporting
confidence: 74%
“…However, what has not yet been as widely reported in the ERPP research to date is the extent to which the role of the supervisor is conducive to the fostering of publishing scholars beyond the supervisor-student relationship. To that extent, the research reported here contributes to furthering insight into that relationship, and is consistent with Lei and Hu's recent study in China [21], in which a similar proportion of participants (only 2 of 11 supervisees) reported any sort of systematic publishing guidance by supervisors.…”
Section: Discussionsupporting
confidence: 74%
“…This suggests that the CIPSE approach can contribute effectively to two of the types of educational intervention posited as useful by : explicit teaching and mentoring programs. The role of the thesis supervisor as mentor is clearly important in supporting first publication efforts by research students in the sciences (Lei & Hu, 2015). Recommendations to the institution by our participants included continuing the training of mentors using workshops like the one run in 2014 until a ratio of 1:5 is reached.…”
Section: Discussionmentioning
confidence: 99%
“…Hard science students also highly value the help of their supervisors in correcting the style and language of their foreign language articles (they rated it as the second most important aspect), while the students in the soft sciences expect their supervisors to help with improving the style and language of their Hungarian articles. Studies have shown that the supervisor is a major factor in research performance, which is measured mainly in publications (Gu, Lin, Vogel, & Tian, 2011;Lei & Hu, 2015) and these data show that Hungarian doctoral students expect their supervisors to assist them with successful publication. In general, students also said that their supervisors actually performed these activities, although some students felt that their supervisors could improve in certain areas.…”
Section: Support In Publishing Activitiesmentioning
confidence: 96%